The 13-minute murder eaudiobook - Patterson, James (BookShots., 2019)
A psychiatrist, a mother, and an expert hitman each race against time in these three fast-paced thrillers from the world's #1 bestselling writer, James Patterson. Dead Man Running: Psychiatrist Randall Beck specializes in PTSD cases — and his time is limited. Especially when he uncovers the plot to kill a presidential candidate. 113 Minutes: Molly Rourke's son has been murdered — and she knows who's responsible. Now she's taking the law into her own hands. Never underestimate a mother's love. 13-Minute Murder : Michael Ryan can kill anybody in just minutes — from the first approach to the clean escape. His skills have served him well, and he has a grand plan: to get out alive and spend his earnings with his beloved wife, Maria. An anonymous client offers Ryan a rich payout to assassinate a target in Harvard Yard. It's exactly the last big job he needs to complete his plan. The precision strike starts perfectly, then somehow explodes into a horrifying spectacle. Ryan has to run and Maria goes missing. Now the world's fastest hit man sets out for one last score: Revenge. And every minute counts.